Penile secondary lesions: a rare entity detected by PET/CT - Tima Davidson (Nature Portfolio, 2021)
Abstract While penile metastases are rare, PET/CT has facilitated their detection. We aimed to describe penile secondary lesions (PSL) identified by PET/CT. We reviewed 18F-FDG and Ga68-PSMA PET/CT records performed in a single center during May 2012-March 2020, for PSL. Of 16,774 18F-FDG and 1,963 Ga68-PSMA-PET scans, PSL were found in 24(0.13%) men with a mean age of 74. PSMA detected PSL in 12 with prostate cancer; FDG identified PSL in 4 with lymphoma, 3 with colorectal cancer, 2 with lung cancer, and one each with bladder cancer, pelvic sarcoma, and leukemia. Mean SUVmax of PSL was 7.9 ± 4.2 with focal uptake in 13(54%). Mean lesion size was 16.5 ± 6.8 mm; 8 at the penile root, 4 along the shaft, and 1 at the glans. CT detected loss of the penile texture in 15(63%). PSL were observed only during relapse or follow-up of disseminated disease. Among those with prostate cancer, PSA varied widely. Fifteen (62.5%) died, at a mean 13.3 ± 15.9 months following PSL demonstration, nine had non-prostate malignancies. PET/CT identified and characterized PSL in a fraction of cancer patients, most commonly those with prostate cancer. PSL universally surfaced in advanced disease, and signaled high mortality, especially in non-prostate cancers.